Evaluation of the Anti Premanism, Drugs and Crime Policy Program in the Bali Regional Police - I Putu Ika Prabawa Kartima Utama; Fibria Indriati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Bali Regional Police (Polda Bali) is in charge of security and public order from various forms of security disturbances. This sense of security is a right for the people in the Bali Region. Moreover, Bali is one of the tourist destinations both local and foreign. Eradication of thuggery and illicit drug trafficking has been a priority program for the Bali Police since 2017. This program was created because previously acts of thuggery and illicit drug trafficking were very disturbing to the Balinese people. Illegal levies to small communities, street crimes that have resulted in loss of life and many Balinese people who are victims of illicit drug trafficking were the face of Bali before the anti-thuggery and drug programs. When this program is run, many changes have occurred until 2020. So that in 2021, this policy program is expected to continue to be a priority policy program for the Bali Police Chief. This is due to the enthusiasm of 97.9% of the 6,050 Balinese people who were the sample of the author's research, the tendency to still want the sustainability of this program. In addition, Balinese people tend to think that the success of eradicating thuggery and drugs by the Balinese police has been very good. This was also confirmed by community leaders from each district/city in Bali who said that the anti-thuggery and drug policy program needed to be maintained and improved.